The impact of low-temperature tolerance on the environmental plasticity indicators of winter bread wheat in the context of climate change - Yarosh, Andrii; Riabchun, Nataliia; Riabchun, Viktor; Kuzmyshyna, Nataliia; Solonechna, Olha (Problems of Cryobiology and Cryomedicine, 2026)
This study examines how low-temperature tolerance influences environmental plasticity of winter bread wheat — a critical factor for crop homeostasis amid global warming challenges. Among winter wheat genotypes graded by hypothermia tolerance, 19.0 % demonstrated the highest environmental plasticity for yield. Genotypes with superior genetic potential adaptability (identified by the lowest rank sums (rank sum = 2) of genotypic effect and regression coefficient (Oktava Odeska, Pontiyka, Zamolxe, NE 10507) yielded 128–148 % related to the check cultivar. In the winter bread wheat cultivars under investigation, there was a moderate negative correlation between freezing tolerance of winter bread wheat leaves in early spring and rank sum of genotypic effect and yield plasticity (r = –0.42; P < 0.05) and a moderate positive correlation between tolerance to critical freezing temperatures and rank sum of genotypic effect and yield plasticity (r = 0.41; P < 0.05). The selected winter bread wheat genotypes with high genetic potentials of environmental plasticity represent high-value starting materials for breeding new wheat cultivars that would be adaptable to current climatic changes. Probl Cryobiol Cryomed. 2025; 35(3): 138—148